Increasing Students’ Readiness and Competencies in Learning Process through Intellectual Diary (ID) - Farid Muhamad (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
The purpose of this paper is to discuss the advantages of students’ intellectual diary (ID) to overcome the major problems of the inadequate competencies of the students in the learning process. For at least 2 years teaches literature subjects in English Education Study Program (EESP), the writer found that most of the students tend to be passive in the classroom. It caused by their lack of motivation to read the material based on the topic discussion, in the meantime the syllabus and teaching material already given to the students. Consequently, as a compulsory, all students should read the teaching material as proved by their ID in handwriting form based on the topic of discussion. The writer adapts this method based on the experiences when studied in UGM. This method increases students’ readiness toward subject in the teaching process. The formulations of the ID become a source of information to the students. Thus, students can give their arguments related to the topic because they already studied earlier rather than waiting what will explained by the lecturer. Furthermore, they also could learn individually the material and if they found difficulties they will discuss it in the teaching process. As consequences, it will bring a good impact to the increases of the student language awareness.